2007
DOI: 10.1088/0960-1317/17/7/014
|View full text |Cite
|
Sign up to set email alerts
|

Automated assembly of hingeless 90° out-of-plane microstructures

Abstract: A novel design for hingeless out-of-plane microstructures is presented. These structures can be assembled to 90° by a single-point actuation, which can be provided by, for example, a microelectronics wirebonder or a microprober station. Both wirebonders and microprober stations are commonly available to microfabrication facilities, and therefore the assembly method described here introduces a practical and economical approach to the creation of out-of-plane structures. The microstructure designs can be used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…These elastic instabilities offer a new form of actuation. For example, buckling, as a design principle, has been used to actuate soft robots, to make tunable metamaterials, to fabricate complex micro/nanomaterials, and control adhesive surfaces . We have demonstrated that reversible buckling of elastomeric beams may be employed for torsional soft actuators by applying negative pressure to an elastomeric structure made of interconnected cavities that reversibly deform, and for linear actuators inspired by muscle …”
mentioning
confidence: 99%
“…These elastic instabilities offer a new form of actuation. For example, buckling, as a design principle, has been used to actuate soft robots, to make tunable metamaterials, to fabricate complex micro/nanomaterials, and control adhesive surfaces . We have demonstrated that reversible buckling of elastomeric beams may be employed for torsional soft actuators by applying negative pressure to an elastomeric structure made of interconnected cavities that reversibly deform, and for linear actuators inspired by muscle …”
mentioning
confidence: 99%
“…As demonstrated by Tsang et al, 23 various SU-8 planar components attached to long serpentine springs were fabricated and anchored to the substrate. The out-of-plane assembly of these components was accomplished by pushing the planar structures laterally until they rotated to the desired 901 position.…”
Section: Parts and Actuatorsmentioning
confidence: 99%
“…The test structures were then placed on microstructures, which could be manually assembled vertical to the substrate after fabrication [7]. Using the vertical stages, side view of the curvature test structures was captured (figure 5), which was analyzed for curvature measurements and geometrical parameter extractions.…”
Section: Test Structuresmentioning
confidence: 99%
“…Research areas that can benefit from three-dimensional microstructures are micro-optics, micro-sensors, micro-actuators, and micro-antennas. MEMS structures can be either assembled after fabrication is completed [7] or during a fabrication process [1,8]. These two types of assemblies can be either assisted by external means [7,8] or developed from stress induced within the structures [1,9].…”
Section: Introductionmentioning
confidence: 99%